The Effect of Maternal Smoking on the Height, Weight and Apgar Scores of the Newborn and on Placental Parameters - Sinan Karadeniz; Metin Altay; Yeşim Bayoğlu Tekin; Necdet Kocabıyık; Hasan Ozan; Orhan Gelişen (Medical Network, 2010)
OBJECTIVE: The aim of this study was to evaluate the effect of smoking on weight, length, 1. and 5. minute apgar scores of newborn and weight, surface area, number of cotyledon of placenta, and coiling index of umbilical cord. STUDY DESIGN: This study was run in Etlik Zübeyde Hanım Maternity And Women's Health Academic and Research Hospital and Gülhane Military Medical Academy Department of Anatomy between January 2003 to January 2004 and perfomed on 258 freshly delivered human placentas. The collected placentas were examined macroscopically, after removing the excess blood, and membrane and the umbilical cord was cut at 1 cm from the placental disc. In order to see if maternal smoking influences newborn and placental parameters, patients were divided into two groups: habitual smokers (46 women) and non-smokers (212 women) and these groups were compared according to placental parameters and newborn APGAR scores,weight and length of newborn. RESULTS: It is determined that placental surface area and Apgar score at 1minute were statistically different among the groups (p<0.05). Number of cotyledon, placental weight, coiling index of umblical cord, fetal length and weight and Apgar at 5 minutes were not different between smokers and non-smoker mothers. CONCLUSION: Smoking seems to effect placental surface area and neonatal Apgar score at 1 minute. Large randomized prospective studies are needed to reveal exact relationship between maternal smoking and fetal placental parameters.